2021
DOI: 10.3390/ma14113024
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Evaluation of Hydrothermal Liquefaction Char from Alkali Lignin in Subcritical Temperatures

Abstract: An evaluation of hydrothermal liquefaction (HTL) char is investigated in this work. Morphological studies, N2 adsorption behavior, FTIR analysis, thermal behavior, and elemental composition are studied. The HTL char yield showed an increase with higher operating temperatures. It increased from 11.02% to 33% when the temperature increased from 573 K to 623 K. At lower temperatures, the residence time showed an impact on the yield, while close to the critical point, residence time became less impactful. Elementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…The hydrochar produced under HTL conditions was mainly secondary hydrochar formed from repolymerization and carbonization of hydrolysis intermediates of lignin via radical reactions . Jayathilake et al found that the yield of hydrochar increased from 11% at 300 °C to 33% at 350 °C of HTL . The increasing residence time from 10 to 30 min slightly increased the yield of hydrochar at 300 and 330 °C of HTL.…”
Section: Hydrothermal Treatment Of Model Compounds To Chemicals Fuels...mentioning
confidence: 85%
See 2 more Smart Citations
“…The hydrochar produced under HTL conditions was mainly secondary hydrochar formed from repolymerization and carbonization of hydrolysis intermediates of lignin via radical reactions . Jayathilake et al found that the yield of hydrochar increased from 11% at 300 °C to 33% at 350 °C of HTL . The increasing residence time from 10 to 30 min slightly increased the yield of hydrochar at 300 and 330 °C of HTL.…”
Section: Hydrothermal Treatment Of Model Compounds To Chemicals Fuels...mentioning
confidence: 85%
“…The increasing residence time from 10 to 30 min slightly increased the yield of hydrochar at 300 and 330 °C of HTL. However, there was no effect of residence time under subcritical conditions . The formation mechanism of hydrochar during HTL conditions included solid-to-solid (undissolved lignin) and dissolution-formation (hydrolyzed lignin) pathways, which is similar to that of HTC of lignin .…”
Section: Hydrothermal Treatment Of Model Compounds To Chemicals Fuels...mentioning
confidence: 91%
See 1 more Smart Citation
“…Higher pyrolysis temperature resulted in an elevation of carbonized fractions, surface area, volatile matter, and pH and a decrease in surface functional groups and CEC (Tomczyk et al, 2020). Additionally, ester groups, aliphatic alkyls, and exposure to aromatic lignin core under high temperatures may increase the surface area (Jayathilake et al, 2021). Ambaye et al (2021) reported that at low temperatures/slow pyrolysis, lignin content is not converted into hydrophobic PAHs and BC develops more hydrophilic characteristics.…”
Section: Pyrolysis Temperaturementioning
confidence: 99%
“…[ 24 ] HTC accommodates a broad range of feedstocks including wet feedstock sources like sugar cane bagasse, [ 25 ] and lignin. [ 26 ] The advantage of this process is using wet biomass compared to pyrolysis which uses dried stock saving the cost of energy required for drying. The pressurized condition for the process is a major challenge leading to complicated process equipment making it expensive compared to conventional pyrolysis.…”
Section: Biomass To Biocarbon Conversionmentioning
confidence: 99%